African sandstorms, blood rain and continental mineral delivery to the Canary Islands. (15th December 2022) - Troll, Valentin R.; Carracedo, Juan Carlos; Gilg, H. Albert
Abstract : The origin of volcanism in the Canary Islands has been a matter of controversy for decades. Discussions have hinged on whether the Canaries owe their origin to seafloor fractures associated with the Atlas Mountain range or to an underlying plume or hotspot of uprising hot material from the deep mantle. The debate has recently concluded, however, following the discovery of nannofossils preserved in the products of the 2011–2012 submarine eruption at El Hierro, which constrain the age and growth history of the westernmost island of the archipelago and so cement a clear East to West age progression within the archipelago. Light‐coloured, quartz‐bearing pumice‐like 'floating rocks' (xeno‐pumice) were found on the sea surface during the first days of the 2011 El Hierro eruption and proved to be fragments of pre‐island, sedimentary strata that were picked up by ascending magma. Upper Cretaceous to Pliocene calcareous nannofossils such as coccolithophores were retrieved from the xeno‐pumice fragments, and these marine micro‐organism biostratigraphical markers now provide crucial evidence that island growth at El Hierro commenced in the Pliocene. Here we discuss how these essentially continental (quartz‐bearing) sediments on the African continental shelf derive from dominantly wind‐blown Sahara dust and marine (re)‐deposition and describe present‐day aeolian processes that are in operation in the region. We investigate the mineralogy of Sahara dust that is currently deposited in the Canary Islands and discuss source areas and intra‐transport fractionation of mineral dust during trans‐Atlantic transport. Finally, we explore how present‐day dust deposition can be used as analogue to explain the deposition of pre‐island continental material in the East‐Atlantic Ocean basin beneath the Canary archipelago and we show how the dust‐derived sedimentary deposits can be utilized as geological tool in the Canary Islands.